APLICAÇÃO DE PIRIDOXINA SOBRE O CRESCIMENTO E PRODUTIVIDADE DA SOJA - Meira, Leonardo Borges Vasconcelos,; TENÓRIO, João Pedro Barreto,; VENDRUSCOLO, Eduardo Pradi,; BORTOLHEIRO, Fernanda Pacheco de Almeida Prado,; MARTINS, Murilo Battistuzzi,; SERON, Cássio de Castro, (ANAIS DO ENIC, 2025)
-